The impact of cystic fibrosis- and noncystic fibrosis-bronchiectasis on pulmonary artery wall thickness and right heart functions assessed by speckle-tracking echocardiography - GÜREL, YUSUF EMRE; VEZİR, DUYGU; KOCAKAYA, DERYA; SÜNBÜL, MURAT; ÇİNÇİN, AHMET ALTUĞ; ÖZBEN SADIÇ, BESTE; SAYAR, NURTEN; CEYHAN, BERRİN (My University, 2023)
BACKGROUND: Right heart functions are affected in patients with bronchiectasis as a result of pulmonary hypertension induced by chronic hypoxemia. Pulmonary artery wall thickness has recently been introduced as a sign of intensive and prolonged inflammation. The aim of this study was to analyze right ventricular and right atrial functions and to mea-sure pulmonary artery wall thickness in patients with cystic fibrosis-bronch iecta sis in comparison to those with noncystic fibrosis-bronchiectasis and healthy individuals. METHODS: We studied 36 patients with cystic fibrosis-bronchiectasis, 34 patients with noncystic fibrosis-bronchiectasis, and 32 age- and sex-matched control subjects. Lung function tests were performed. All subjects underwent comprehensive echocardiographic evaluation including conventional, tissue Doppler, speckle-tracking, and pulmonary artery wall thickness measurements. RESULTS: Right ventricular global longitudinal strain and global longitudinal right atrial strain during ventricular systole decreased in cystic fibrosis-bronchiectasis group compared with noncystic fibrosis-bronchiectasis and control groups (P <.001, both). Conversely, pulmonary artery wall thickness was increased in cystic fibrosis-bronchiectasis group in comparison to other groups (P <.001). Moreover, right ventricular global longitudinal strain was lower and pulmonary artery wall thickness was higher in patients with airflow obstruction (P <.001 and P =.025, respectively) than in those without. Only right ventricular global longitudinal strain was significantly correlated with pulmonary function test parameters. The negative effect of cystic fibrosis on right ventricular and right atrial functions was independent of age, gender, and disease duration. CONCLUSION: Our study showed that right ventricular and right atrial functions were deteriorated and pulmonary artery wall was thickened in cystic fibrosis-bronchiectasis patients more than noncystic fibrosis-bronchiectasis patients. Right ventricular global longitudinal strain detected subclinical right ventricular dysfunction and was associated with the severity of pulmonary disease.
Keywords: Tıp; Dahili Tıp Bilimleri; Kardiyoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Cardiovascular; Health Sciences; Klinik Tıp (MED); Klinik Tıp; KALP VE KALP DAMAR SİSTEMLERİ; Clinical Medicine (MED); CLINICAL MEDICINE; CARDIAC & CARDIOVASCULAR SYSTEMS; Kardiyoloji ve Kardiyovasküler Tıp; Cardiology and Cardiovascular Medicine; Chronic diseases; echocardiography; pulmonary circulation and right ventricle